Microstructural refinement and texture enhancement of ER 5356 aluminium alloy by hybrid WAAM-forging - Musa, Nornisaadila; Adenan, Mohd Shahriman; Sadeon, Juri (UiTM Press, 2026)
Wire arc additive manufacturing (WAAM) is a promising technique for fabricating aluminium alloy components due to their high strength-toweight ratio and good machinability. However, challenges such as porosity and the formation of coarse columnar grains occurring from rapid solidification hinder its broader application. This study investigates a hybrid WAAM-forging approach with the aim of reducing porosity and modifying crystallographic texture in ER5356 aluminium alloy. Comparative analyses were conducted on as-deposited and WAAM-forged samples using scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), and density analysis for characterisation. Results indicate that WAAM-forging significantly refines grain structure, mitigates columnar grain alignment, and promotes more homogeneous texture distribution. Kernel average misorientation (KAM) analysis reveals a lower degree of local misorientation in forged samples, suggesting effective stress relaxation. The pole figure analysis confirms a suppression of strong texture components, particularly in the {100} and {111} orientations, potentially reducing anisotropy in mechanical properties. The hybrid WAAM-forging process demonstrates significant improvements in the structural integrity and performance of WAAM-fabricated aluminium components, particularly through a reduction of porosity from 4.05% to 2.13% and a refinement of grain size from 168 μm to 122 μm. These findings contribute to the advancement of hybrid additive manufacturing strategies for high-performance applications.